Nitrogen oxide gas sensor based on metal oxide thin film - Mubin, M. Helmi (American Scientific Publishers, 2018)
Indium tin oxide (ITO) thin films of different thicknesses are grown on the corning glass substrates using radio frequency (RF) magnetron sputtering. The variation in resistance of deposited thin films relative to nitrogen oxide (NO2) at different operating temperatures is measured. The sensitivity of grown thin films as NO2 sensor is investigated in single layer and sensory array configurations. The high sensitivity is observed for thin film with thickness 227 nm is 1.440 as single layer configuration and 2.065 as series array combination of thin films with thickness 132 nm +424 nm. The response time, reproducibility and recovery time are determined relative to NO2 gas sensing behavior of the fabricated film. The response and recovery times determined for single layer configuration are 108 and 240 seconds respectively whereas for array configuration are 60 and 600 seconds respectively. A very stable reproducibility response towards NO2 gas sensing is observed.